2018
DOI: 10.4103/jehp.jehp_25_17
|View full text |Cite
|
Sign up to set email alerts
|

Internationalization or globalization of higher education

Abstract: INTRODUCTION:Studies about globalization and internationalization demonstrate different attitudes in explaining these concepts. Since there is no consensus among Iranian specialists about these concepts, the purpose of this study is to explain the concepts of internationalization and globalization in Iran.MATERIALS AND METHODS:This study is a systematic review done in the first half of 2016. To explain the concept of globalization and internationalization, articles in Scientific Information D atabase, Magiran … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…China has become one of the popular study hubs for international students as a result of the recent call for the internationalization and globalization of our world [1]. In 2015 alone, China’s Ministry of Education reported a total of 397,635 overseas students enrolled in various institutions.…”
Section: Introductionmentioning
confidence: 99%
“…China has become one of the popular study hubs for international students as a result of the recent call for the internationalization and globalization of our world [1]. In 2015 alone, China’s Ministry of Education reported a total of 397,635 overseas students enrolled in various institutions.…”
Section: Introductionmentioning
confidence: 99%
“…However, social science studies of globalisation have shown economic, cultural and political factors to be closely connected in the globalisation processes (see, for instance, Giddens, 1999; Robertson, 1992). Rezaei et al (2018) include another factor in the definitions of globalisation: the scientific dimension.…”
Section: Globalisation and Internationalisation: In Search Of A Balan...mentioning
confidence: 99%
“…There are two approaches to globalisation. The first approach is related to colonialism, where a dominant economy shapes the economy and culture of other countries (Rezaei et al, 2018). Hence, internationalisation aligns the patterns of the dominant culture to that of the other countries.…”
Section: Globalisation and Internationalisation: In Search Of A Balan...mentioning
confidence: 99%
See 1 more Smart Citation
“…If CR < 0.1, it has passed the consistency test. All quality factors which are shown in Figure 7 are selected from different studies [66][67][68][69][70][71][72][73][74][75][76][77][78] with each factor is highlighted against its study. Otherwise, it has failed.…”
Section: Step 5: Swot Matrix For Decision-makingmentioning
confidence: 99%